ANALISIS RANTAI NILAI PADA PERUM PERHUTANI DALAM MENENTUKAN PRODUK UNGGULAN - SASONGKO JATI, LINGGAR; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2018)
This research uses descriptive qualitative research approach in analyzing the activity of value chain of company. Research begins with identifying value chain activities by classifying each activity into key activities and supporting activities. The next step is to identify each value activity and the next step is to identify opportunities to add value. The procedure of data retrieval is done by observation, interview and documentation. Based on the results of the identification then carried out the analysis. The results showed that on the main activities and supporting activities of Perum Perhutani KPH Bojonegoro there execution of activities of less efficient value. Companies are better off reducing the activity that arises from each value activity. With the implementation of efficient value activity the company can change the value of activity from Perum Perhutani KPH Bojonegoro can be improved. Keywords: value chain analysis, Premium Gods